THIRD-PARTY FUNDS, CAPITAL ADEQUATE RATIO, PROFIT-SHARING FINANCING, AND NON-PERFORMING FINANCING ON PROFITABILITY IN SHARIA COMMERCIAL BANKS IN INDONESIA - Siti Maesaroh (Journal Of Communication Education, 2023)
This study aims to examine whether there is an influence from the mechanism of Third-Party Funds, Capital Adequate Ratio (CAR), Profit sharing financing, and Problematic financing on profitability in Islamic commercial banks for the period 2016-2020 with a total sample of 8 Islamic commercial banks in Indonesia. The analysis used in analysis multiple linear regression with the SPSS 18.00 analysis tool. The results of the data test stated that the f-test showed that all variables affected the profitability of Islamic commercial banks in Indonesia. Whereas through the t-test the variables of Third-party Funds (DPK), Capital Adequate Ratio (CAR), and profit-sharing financing have no effect on profitability in Islamic commercial banks in Indonesia while Non-Performing Financing (NPF) has an influence on profitability in Islamic commercial banks in Indonesia. Keywords: Third Party Funds, Capital Adequate Ratio, Profit sharing financing, Non Performing Financing, Profitability